From the series: cultural trends. New locations of cities - Nowina-Sroczyńska, Ewa (A mosaic city: The culture-oriented description, 2023)
One of the hottest cultural trends of recent years is set-jetting, tourism to places we have come to know thanks to filmmakers. The cities in my anthropological story get their start from cinema. In the text I discuss one exemplification: Sandomierz, whose tourist revitalisation was achieved thanks to cinema. Jean Baudrillard and his theory of simulation and precession of simulacra helped me unravel the problem.